Generation Z Information Seeking Behavior on Tourist Destinations During The Covid-19 Pandemic - Prasetyo, Hendi; Makiya, Kiki Rizki (International Journal Of Tourism, 2023)
Information-seeking behavior skills related to tourist destinations by Generation Z during the Covid-19 pandemic are highly needed. This study aims to determine the information-seeking behavior skills related to tourist destinations by Generation Z during the Covid-19 pandemic. The researcher employed a quantitative method with descriptive analysis using the mean and grand mean. The research findings indicate that overall, the information-seeking behavior skills of Generation Z travelers in searching for information related to tourist destinations are categorized as good, with a grand mean value of 3.90 from all tested indicators, including previous visits, engagement, deliberate learning, incidental learning, familiarity, expertise, internal search costs (cognitive effort required and expected outcomes), and external search costs (involving significant time and various sources).